Shaken Baby Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Non-accidental head injury, with particular reference to whiplash shaking injury, is reviewed by paediatric neurologists at the Royal Hospital for Sick Children, Edinburgh.